RESEÑA de: Antonio García-Pablos de Molina. "Introducción al Derecho penal". Editorial Universitaria Ramón Areces, Madrid, 3ª ed., 2005. 815 páginas - Guzmán Dalbora, José Luis (Revista de Derecho Penal y Criminología, 2019)
-